ANALISIS PENERAPAN LAPORAN LABA RUGI BERDASARKAN SAK EMKM PADA USAHA SASA RESTO DI KOTA METRO - Lella Anita (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2022)
This study aims to overcome the problem of financial recording by MSME owners who do not yet have a good financial reporting system for reporting according to SAK. SAK EMKM is a financial standard designed for MSMEs to facilitate financial reporting. This study uses qualitative research with a case study approach. The steps include interviews, documentation, and transaction data processing to fulfill SAK EMKM. The results of the study show that the Sasa Resto business still keeps financial records manually and fundamentally. The reason for recording this simple report is due to the lack of knowledge of business owners in preparing standard financial reports and limited time availability. The merger of SAK EMKM has not yet been implemented.